Influence of Long-term Use of Organic and Inorganic Nutrients on HLB Disease of Wheat under Rice-Wheat Cropping Pattern - Bhandari, Deepak; Regmi, Anant P. (Nepal Agriculture Research Journal, 2014)
Helminthosporium leaf blight (HLB) is one of the most destructive diseases of wheat in terai (plain) region of Nepal. This study was conducted to determine the effect of long-term application of various levels of nitrogen (N), phosphorus (P), potassium (K) and organic nutrients on HLB disease of wheat. The experiment was superimposed on long-term fertility experiment conducted in RCB design with three replications under rice-wheat cropping pattern at National wheat research program (NWRP), Bhairahawa, Nepal. The treatments include various combinations of nitrogen 100 kg ha-1, phosphorus 0 and 60 kg ha-1, and potash 0, 50 and 100 kg ha-1 with or without Sesbania (Sesbania cannabina) and farm yard manure (FYM). Area under disease progress curve (AUDPC) was calculated using the disease scores and yield parameters were recorded. Among the inorganic nutrients, long-term deficiency of potash in the field markedly enhances the HLB disease. Application of phosphorus in various doses increased the HLB severity in absence of potash. Regular application of at least potash 50 kg ha- 1 in wheat noticeably reduced the HLB disease. Regular use of FYM 10 ton ha-1 for long-term considerably reduced the HLB disease but long-term use of Sesbania as green manure did not show any impact on HLB severity. Inclusion of potash in nutrients considerably increased the yield and thousand grain weight (TGW) of wheat. In long term, balanced use of inorganic and organic nutrients with special attention on regular inclusion of potash and FYM in the nutrient combinations is vital in suppression of HLB disease under rice-wheat cropping pattern. Nepal Agric. Res. J. Vol. 9, 2009, pp. 76-84 DOI: http://dx.doi.org/10.3126/narj.v9i0.11644